HISTORICAL DEVELOPMENT OF COST ACCOUNTING. - Garner, S. Paul (The Accounting Review, 1947)
Abstract This brief survey will serve to indicate that cost accounting is not a newly developed off- spring from its parent, the accounting process, but rather has been going through its "growing pains" for many decades. In view of its long and interesting evolution, the Committee feels that cost accounting now occupies such a prominent place in the business community that it is opportune and highly desirable for its principles and concepts to be stated in tentative form. Or, to express it differently, the Committee believes that cost accounting has now "grown up" sufficiently to warrant the serious attention which the Committee has given to its area and purposes. The present paper, therefore, will attempt to set the stage for those to follow, and show that many of the cost accounting developments which are often considered to be modern have their genesis in many past decades. It should be emphasized, however, that only the highlights of this evolutionary aspect of cost accounting can be presented in the brief time available. Elaboration on these highlights must be postponed to some future time.